History of the Text and Johannine Exegesis: Jn 13.14 as Test Case - Pastorelli, David (Filología neotestamentaria, 2025)
The idea of a single-form text is misleading. For this reason, we advocate a decompartmentalisation of low and high criticism. The aim of this paper is to provide some elements for reflection based on an example from the account of the washing of the feet: Jn 13.14 is treated as a test case. Our thesis is that these elements have an impact on exegesis and that the commentator benefits from paying attention to them. It requires bringing together three fields of research: textual criticism with its methodology; exegesis; and the history of reception. The 'Western' variants deserve attention from the point of view of the history of the text, because they are repeatedly the oldest and the most widespread. Here the history of reception requires giving due consideration to versions and patristic quotations, particularly in the Syriac and Latin traditions, and the testimony of the Diatessaron (c. 170) in favour of the 'Western' text is decisive. This is why the exegete should be encouraged to comment not only on the Alexandrian text, followed by the current editions, but also to take into account this other form of the text. Here, there are two possibilities. If the 'Western' reading is considered secondary, because it appears very early in the second century, the exegete gains by taking it into account with regard to the history of the reception of the text. If the 'Western' reading is considered original with regard to the establishment of the text, the exegete must comment on it.